Reciprocal force generated by two sliding jigs: An alternative mechanic for molar protraction - Fazlur RNA. Fashih; Alma Kasita; Soekarsono Hardjono; Sri Suparwitri (Journal of Dentomaxillofacial Science, 2021)
Objective: When a first molar is lost, orthodontic replacement with second and third molars would be an excellent treatment option. There are some side effects that tend to occur during molar protraction, such as mesial tipping of molar that could increase the time required to correct. These side effects can be avoided by understanding the biomechanical variables affecting molar protraction. The author tries to present the modification of sliding jigs, instead of the power arm function, with additional of lingual force, for molar protraction.Methods: This case report describes the management of a 23-years-old woman who was missing left mandibular first molar, had class III skeletal profile, and anterior crossbite. After anterior crossbite correction, the left mandibular first molar extraction spaces were closed by protraction of the second and third molars. Mesial tipping was detected in the early protraction phase when using conventional method. Consequently, uprighting procedure was done and protraction was continued using reciprocal force generated by two sliding jigs and lingual buttons to achieve bodily movement of tooth.Results: The result was excellent, the space was closed without tipping and rotation.Conclusion: The presented article provides an alternative mechanic for molar protraction using sliding jigs and how it can be designed to achieve predictable result.